2019
DOI: 10.1080/11101849.2019.1655202
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electric Nerve Stimulation (TENS) for pain relief during Extracorporeal Shock-Wave Lithotripsy (ESWL)

Abstract: Background: Anesthesia for ESWL must provide good analgesia, rapid recovery with least side effects. Opioids are commonly used analgesics during ESWL, but are not devoid of side effects. TENS is a non-pharmacological, non-invasive analgesic technique, which has been recommended for pain control in many clinical settings. Methods: Sixty patients scheduled for ESWL were randomly assigned to group-A (30 patients): received IV fentanyl 1µg/Kg with the application of conventional TENS. Group-B (30 patients) receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…Nociceptive effects are associated with increased blood pressure, respiratory rate, and heart rate [ 34 ]. Pain during ESWL increases the risk of kidney hematoma with increased blood pressure [ 7 ]. Our study revealed significant effects of acupressure on patients' systolic blood pressure during the peak of shockwave energy, which is not consistent with the study of Düzel et al [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nociceptive effects are associated with increased blood pressure, respiratory rate, and heart rate [ 34 ]. Pain during ESWL increases the risk of kidney hematoma with increased blood pressure [ 7 ]. Our study revealed significant effects of acupressure on patients' systolic blood pressure during the peak of shockwave energy, which is not consistent with the study of Düzel et al [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this method inherently causes significant pain; thus, pain relief is recommended for patients during the procedure [ 6 ]. Severe pain might limit the opportunity for applying sufficient energy doses, leading to additional movement and increased respiration rates [ 7 ]. Additionally, acute pain may increase the risk of kidney hematoma following stone fragmentation due to increased blood pressure [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan alternatif (untuk pasien yang refrakter terhadap penggunaan konvensional yaitu menggunakan TENS frekuensi rendah: stimulus dengan lebar pulsa >200 mikrodetik dan frekuensi <10 Hz (selama 5-15 menit). Perhatian dilakukan bahwa efek stimulasi frekuensi rendah setidaknya sebagian dibalik oleh nalokson yang menunjukkan peran opioid endogen (Shoukry & Al-Ansary, 2019).…”
Section: Terapi Nonfarmakologisunclassified